Remains of the Social : Desiring the post-apartheid - Lalu, Premesh; Minkley, Gary; Truscott, Ross; Van Bever Donker, Maurits M.; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2017)
Remains of the Social is an interdisciplinary volume of essays that engages with what 'the social' might mean after apartheid, a condition referred to as 'the postapartheid social'. The volume grapples with apartheid as a global phenomenon that extends beyond the borders of South Africa between 1948 and 1994 and foregrounds the tension between the weight of lived experience that was and is apartheid, the structures that condition that experience, and a desire for a 'post-apartheid social'. Collectively, the contributors argue for a recognition of 'the post-apartheid' as a condition that names the labour of coming to terms with the ordering principles that apartheid both set in place and foreclosed. The volume seeks to provide a sense of the terrain on which 'the post-apartheid' - as a desire for a difference that is not apartheid's difference - unfolds, falters and is worked through.
Traversing the social / Maurits van Bever Donker [and three others] -- The Mandela imaginary : reflections on post-reconciliation libidinal economy / Derek Hook -- The return of empathy : postapartheid fellow feeling / Ross Truscott -- The ethics of precarity : Judith Butler's reluctant universalism / Mari Ruti -- Hannah Arendt's work of mourning : the politics of loss, 'the rise of the social' and the ends of apartheid / Jaco Barnard-Naud{acute}e -- Souvenir / Annemarie Lawless -- Re-cover : Afrikaans rock, apartheid's children and the work of the cover / Aiden Erasmus -- The graves of Dimbaza : temporal remains / Gary Minkley and Helena Pohlandt-McCormick -- The principle of insufficiency : ethics and community at the edge of the social / Maurits van Bever Donker -- The Trojan Horse and the 'becoming technical of the human' / Premesh Lalu.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Post-apartheid era -- South Africa; South Africa -- Social conditions -- 1994-; Electronic books